The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/mbp.0b013e32832e2a40
|View full text |Cite
|
Sign up to set email alerts
|

Influence of home blood pressure measuring conditions in the evening on the morning–evening home blood pressure difference in treated hypertensive patients: the J-HOME study

Abstract: Measurement of evening BP after drinking and measurement of evening BP after bathing were strongly associated with an increased home systolic ME dif, independent of morning and evening home BP levels. Therefore, evening home BP measuring conditions (before or after drinking alcohol and bathing) should be taken into account while evaluating the home systolic ME dif.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Moreover, most of the studies on MH have previously been performed with HBPM system, which is the method used in our study. Furthermore, we did not obtain information about alcohol consumption, which has been associated with variations in BP measurements 33 and MH 29 . In addition, smoking habits were not identified in data gathering of this study.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, most of the studies on MH have previously been performed with HBPM system, which is the method used in our study. Furthermore, we did not obtain information about alcohol consumption, which has been associated with variations in BP measurements 33 and MH 29 . In addition, smoking habits were not identified in data gathering of this study.…”
Section: Discussionmentioning
confidence: 91%
“…Excessive reductions in blood pressure (BP) might be a causative factor in cases of drowning in hot water; therefore, it is important to understand the extent to which central BP decreases after bathing in hot water to prevent individuals from drowning. In addition, during home BP monitoring, Japanese patients tend to show lower BP in the evening than in the morning, and this might be partly because of their habit of bathing in hot water at night [2,3]. Therefore, the aim of this study was to evaluate the magnitude of the reduction in central BP observed after bathing in hot water and to evaluate whether evening BP or night-time BP differs between bathing and nonbathing days.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that BP values obtained after drinking or taking a bath are lower than BP values obtained before drinking or taking a bath [31,32,33]. In the J-HOME study, we also reported that measurement of evening BP after drinking and measurement of evening BP after bathing were strongly associated with an increased morning-evening home systolic BP difference [16]. Furthermore, this discrepancy might be due to inappropriate drug administration over the 24-hour period and would call for a better distribution of drugs and/or doses over the 24–hour period [34].…”
Section: Discussionmentioning
confidence: 96%